Error description of the first year student in aljabar problems - Sri Rahmawati Fitriatien (Math Didactic: Jurnal Pendidikan Matematika, 2019)
This research is aimed to describe the cause of failure in mathematics for students at college. The error analysis used by researchers was based on Newman's analysis with the stages of reading, understanding, transformation, process skills, and writing answers. This research was conducted on the students of University of PGRI Adi Buana Surabaya who study for two semesters. The data collection technique used by researchers was by test and interview techniques in which to determine the accuracy and the result of the data, the researcher carried out a triangulation process of the two techniques. The result of this research used by third students who have lowest grade. The results of this study indicate that the first subject and the third subject make a type of error at the reading stage, understanding, transformation, process skills, and writing answer. While for the second subject types of error made in solving mathematical story problems are at the stage of transformation and process skills. Some of the factors that cause this error include students who do not understand the meaning of some of the sentences the question, the students do not know the information the complete of question, students do not know the formula to be used, students do not take appropriate algebraic steps, and students do not understand the final step of the question.